Review of energy storage systems for electric vehicle applications: Issues and challenges - Hannan M.A.; Hoque M.M.; Mohamed A.; Ayob A. (Elsevier Ltd, 2023)
Carbon; Electric power transmission; Electric vehicles; Energy resources; Energy storage; Gas emissions; Greenhouse gases; Power electronics; Storage (materials); Vehicles; Alternative energy resources; Electronic technologies; Energy storage applications; Energy storage systems; Energy Storage Systems (ESSs); Hybridization; Issues and challenges; Vehicle applications; Electric energy storage